Chebyshev Weighted Type Integral Inequality in Fuzzy and Abstract Spaces - Bayaz Daraby; Zahra Vaezi (Sahand Communications in Mathematical Analysis)
In this paper, we express and prove Chebyshev weighted type inequality for fuzzy integrals and in abstract spaces where the functions are strictly monotone functions. Furthermore, we have shown our results for n-th strictly monotone functions. The theorems are illustrated with several examples.